German-Australian Encounters and Cultural Transfers Global Dynamics in Transnational Lands (Global Germany in Transnational Dialogues,, 2018)
This book approaches Australo-German relations from comparative and interdisciplinary perspectives. It maps new pathways into the rich landscape of the Australo-German transnational encounter, which is characterized by dense and interwoven cultural, historical and political terrains. Surveying an astonishingly wide range of sites from literary translations to film festivals, Aboriginal art to education systems, the contributions offer a uniquely expansive dossier on the migrations of people, ideas, technologies, money and culture between the two countries. The links between Australia and Germany are explored from a variety of new, interdisciplinary perspectives, and situated within key debates in literary and cultural studies, critical theory, politics, linguistics and transnational studies. The book gathers unique contributions that span the areas of mig ration, aboriginality, popular culture, music, media and institutional structures to create a dynamic portrait of the exchanges between these two nations over time. Australo-German relations have emerged from intersecting histories of colonialism, migration, communication, tourism and socio-cultural representation into the dramatically changed twenty-first century, where traditional channels of connection between nations in the Western hemisphere have come undone, but new channels ensure cross-fertilization between newly constituted borders.